THE IMPACT OF INSTITUTIONAL LAND USES ON RENTAL VALUE OF RESIDENTIAL PROPERTIES IN AGBANI, ENUGU, NIGERIA - C. O., Aniagolu; E. A., Iyi; A. F., Iloeje (International Journal For Research In Business, Management And Accounting, 2021)
Agbani, Enugu Nigeria was a rural community until three very important institutions were moved by the governor to that location. This study therefore investigates the impact of Institutional Landuses on rental values of residential properties in Agbani. The study tried to determine the trends in rental values of residential accommodations in Agbani before and after the institutions came. It also compared the rent in Agbani with that of surrounding communities of Amuri, Amodu, Ugbawka and Akpugo. The study adopted the survey research methodology and covered tenement rooms, self contained rooms, one bedroom flats, two bedrooms flats and three bedroom flats. Rental survey was carried out between 1999 and 2014. A one way ANOVA was used to test the hypothesis. It was discovered that there was a statistically significant difference between rental values before and after the institutions came. Also the survey shows a significant difference between rental values of residential accommodations in Agbani and that of surrounding communities. The study therefore recommended among other things that institutional landuses should be used as a fulcrum that drives development in under-developed and developing countries of the world.